RELATIONSHIP OF SCHOOL HEAD SUPERVISION AND WORK EFFECTIVENESS WITH TEACHER WORK SATISFACTION, JAGAKARSA JAKARTA - Sumiati SANDA (Journal of Education and Leadership in Education, 2018)
The Relationship principals’ supervision and effectiveness to work with satisfaction working teachers for primary school teachers in territory 2 Jagakarsa, South Jakarta. The research is aimed to find out the correlation between: (1) Principals supervision and satisfaction working teachers; (2) effectiveness to work and satisfaction working; satisfaction working teachers (3) Principals supervision and effectiveness to work with satisfaction working teachers. The research method used was survey method. The population was the primary school teachers in territory 2 Jagakarsa, South Jakarta and the sample was chosen random for 100 teachers. The data were taken by using questionnaire and were analyzed statistically by using correlation and regression with the significance level of 0.05. The research findings were drawn as follow: (1) There was positive significance corellation between Principals supervision and satisfaction working teachers with simple regression Ŷ= 27.54 + 0.70X1 and partial correlation ry1.2 = 0.640. (2) There was positive significance corellation between effectiveness to work and satisfaction working; satisfaction working teachers with simple regression Ŷ= 15.60 + 0.81X2 and partial correlation ry1.2 = 0.669. (3) There was positive significance corellation between Principals supervision and effectiveness to work with satisfaction working teachers with double correlation coefficience Ry12= 0.707 and double equation regression Ŷ= 7.548 + 0.359X1+ 0.522X2. Based on the research findings between principals’ supervision and effectiveness to work with satisfaction working teachers, the conclusion was stated that were was highly significance correlation.